2012
DOI: 10.1002/humu.22126
|View full text |Cite
|
Sign up to set email alerts
|

PRRT2 Mutations are the major cause of benign familial infantile seizures

Abstract: Mutations in PRRT2 have been described in paroxysmal kinesigenic dyskinesia (PKD) and infantile convulsions with choreoathetosis (PKD with infantile seizures), and recently also in some families with benign familial infantile seizures (BFIS) alone. We analyzed PRRT2 in 49 families and three sporadic cases with BFIS only of Italian, German, Turkish, and Japanese origin and identified the previously described mutation c.649dupC in an unstable series of nine cytosines to occur in 39 of our families and one sporad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 25 publications
4
87
2
Order By: Relevance
“…PRRT2 mutations were clustered in families with BFIE (41 out of 68, 60.3%). It may be due to regional and racial differences, however, our rate was lower than those rates found by other research groups [11,12,14,21]. In our study, most PRRT2 mutations were frameshift mutations.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…PRRT2 mutations were clustered in families with BFIE (41 out of 68, 60.3%). It may be due to regional and racial differences, however, our rate was lower than those rates found by other research groups [11,12,14,21]. In our study, most PRRT2 mutations were frameshift mutations.…”
Section: Discussioncontrasting
confidence: 76%
“…The voltage-gated sodium channel gene SCN2A was identified as the major causative gene for BFNIE [9,10]. Recently studies also led to the identification of mutations in the proline-rich transmembrane protein 2 gene PRRT2 in BFIE [11,12]. However, for some families, the causative genes have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Heron et al identified five different mutations in PRRT2 in 14 of 17 families affected by BIE and in five of six families affected by ICCA [5] and Ono et al found two mutations in PRRT2, c.649_650insC and c.748C>T, in all individuals with PKD and/or BIE [6]. Thereafter, several reports have shown that PRRT2 mutation will be one of the major genes relating to BIE, PKD, and ICCA [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, we hypothesized that PRRT2 mutation may also be related to several phenotypes of infantile epilepsies other than BIE and/or PKD.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, missense mutations in the gene PRRT2 (proline-rich transmembrane protein 2) were described for both paroxysmal kinesigenic dyskinesia and BFIS, and the combination of both called infantile convulsions and choreoathetois (ICCA) [18][19][20][21][22]. The resulting protein might be functionally relevant in the vesicle synaptic metabolism of neurons as it interacts with SNAP25, which is a member of the SNARE complex responsible for the vesicle exocytosis into the synaptic cleft [18].…”
Section: Good Prognosismentioning
confidence: 99%